Carbonic anhydrase versatility: from pH regulation to CO2 sensing and metabolism - Supuran, Claudiu T. (Frontiers in Molecular Biosciences, 2023)
While the carbonic anhydrase (CA, EC 4.2.1.1) superfamily of enzymes has been described primarily as involved only in pH regulation for decades, it also has many other important functions. CO2, bicarbonate, and protons, the physiological substrates of CA, are indeed the main buffering system in organisms belonging to all life kingdoms; however, in the last period, relevant progress has been made in the direction of elucidating the involvement of the eight genetically distinct CA families in chemical sensing, metabolism, and several other crucial physiological processes. Interference with CA activity, both by inhibiting and activating these enzymes, has thus led to novel applications for CA inhibitors and activators in the field of innovative biomedicine and environment and health. In this perspective article, I will discuss the recent advances which have allowed for a deeper understanding of the biochemistry of these versatile enzymes and various applications of their modulators of activity.